2017
DOI: 10.1111/aos.13532
|View full text |Cite
|
Sign up to set email alerts
|

Posterior corneal surface differences between non‐laser in situ keratomileusis (LASIK) and 10‐year post‐LASIK myopic eyes

Abstract: Our results demonstrated that the posterior corneal surface tends to show signs of central flattening and peripheral steepening 10 years after myopic LASIK surgery compared to that of non-operated myopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We found that both procedures showed a statistically significant decrease in CCT, keratometry readings, and ACD values after surgery. Dai ML and associates [25] reported that the ACD was shallower in LASIK than in non-operated myopic eyes.…”
Section: Discussionmentioning
confidence: 96%
“…We found that both procedures showed a statistically significant decrease in CCT, keratometry readings, and ACD values after surgery. Dai ML and associates [25] reported that the ACD was shallower in LASIK than in non-operated myopic eyes.…”
Section: Discussionmentioning
confidence: 96%
“…We found that both procedures showed a statistically significant decrease in CCT, keratometry readings, and ACD values after surgery. Dai ML and associates [25] reported that the anterior chamber depth was shallower in LASIK than in non-operated myopic eyes.…”
Section: Discussionmentioning
confidence: 97%
“…The present study revealed that the posterior surface underwent more oblate changes after surgery, and there were no accidents of keratectasia after refractive surgery. Dai and associates [36] reported that the anterior chamber depth was shallower in LASIK patients than in non-operated myopic eyes. However, in our study results, although there were significant changes in anterior chamber depth after surgery, and there were no statistically significant differences between 2 groups.…”
Section: Discussionmentioning
confidence: 97%